Urea’s Effect on Dry Matter, Organic Matter, and Crude Protein Content of Ammoniated Corn Straw - Azhary Noersidiq; Syamsul Hidayat Dilaga; Suhubdy Suhubdy; Muhamad Amin; Fahrullah Fahrullah; Vebera Maslami (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Feed is an absolute necessity that must be guaranteed in the maintenance of ruminants but its availability is always a problem during the dry season so that a fresh forage is difficult to obtain and only agricultural waste in the form of straw is available. One of widely used by farmers, especially in Lombok region, is corn straw. This research aims to evaluate the nutritional content of corn straw that has been ammoniated using urea. This study used corn straw and urea for the ammoniation process with a complete randomized design (CRD) design consisting of 4 treatments and 4 replications, namely T1= corn straw without ammoniation (control), T2= corn straw ammoniated with a dose of 2% urea, T3= corn straw ammoniated with a dose of 4% urea and T4= corn straw ammoniated with a dose of 6% urea. The variables measured were dry matter (DM), organic matter (OM) and crude protein (CP). The results showed that urea used in the ammoniation process of corn straw showed a significant effect (P<0.05) on increasing the content of DM, OM and CP with results ranging from 21.02% - 23.98% for DM content, 88.13% - 91.07% for OM content and 13.53% - 23.81% for CP content. It was concluded that the best dose of urea for ammoniation of corn straw was treatment T4 with a dose of 6% urea with the results of the content of 23.98% DM; 89.94% OM and 23.81% CP, respectively.